(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
Aedes aegypti and Aedes albopictus mosquitoes spread dengue and yellow fever in Africa and worldwide. Rural-urban drift creates Aedes mosquito breeding sites through uncontrolled urbanization, inadequate urban infrastructure, lack of basic public health delivery, indiscriminate waste disposal, varying socioeconomic activities, and climatic changes. The above have happened in Maiduguri Metropolis since Boko Haram insurgencies began. This study will examine Aedes aegypti’s seasonal distribution, abundance, composition, and genetic variability in selected Maiduguri Metropolitan Council and Jere Local Government Council communities. From October 2016 to May 2017, CDC traps and vacuum aspirators collected adult mosquitoes from study sites and stored at – 80 C. These were identified morphologically with taxonomy keys and stereomicroscopes, then molecularly with markers. Aedes mosquito population structure and genetic variability were determined using statistical software and molecular methods on samples. Hot-dry season has the highest relative abundance of this mosquito species in these study sites, while cold-dry season has the lowest. The molecular identification found Aedes aegypti in nine of twelve study locations but not Aedes albopictus. Some mosquitoes from the study locations had mutations due to carrying dengue virus or host population genes, but those without mutations showed a good phylogenetic relationship with Aedes aegypti mosquitoes from other countries, suggesting no genetic variability. The relative abundance of Aedes mosquitoes in Maiduguri Metropolitan Council increases the risk of dengue, zika, yellow fever, and chikungunya virus infections, and this mosquito species’ seasonal distributions vary within and across seasons, but no genetic variability was found in the mosquitoes from the different locations used in this study.